2023
DOI: 10.1097/htr.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Chronic Pain Experience and Treatment History Among Persons With Traumatic Brain Injury: A Traumatic Brain Injury Model Systems Study

Abstract: Objective: To determine disparities in pain severity, pain interference, and history of pain treatment for non-Hispanic Whites, non-Hispanic Blacks, and Hispanics with traumatic brain injury (TBI) and chronic pain. Setting: Community following discharge from inpatient rehabilitation. Participants: A total of 621 individuals with medically documented moderate to severe TBI who had received acute trauma care and inpatient rehabilitation (440 non-Hispanic Whites, 111 non-Hispanic Blacks, and 70 Hispanics). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…While we found several significant sociodemographic differences between those with current chronic pain, past pain, and no pain, the effect sizes were small and therefore may not be clinically meaningful. This lack of difference may be related to the bivariate approach that we took in describing the sample where these factors may not alone impact whether someone identifies as having current, past, or no chronic pain, especially given that when looking within a subgroup reporting chronic pain disparities were found in reports of the experience of pain 15. However, those with current chronic pain did have significantly worse functional outcomes, with medium effect sizes, as measured by the FIM, DRS, and GOS-E. Further research is needed to determine the nature of this relationship between functional outcomes and the experience of chronic pain, as well as exploration of multivariate models where subgroups may be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we found several significant sociodemographic differences between those with current chronic pain, past pain, and no pain, the effect sizes were small and therefore may not be clinically meaningful. This lack of difference may be related to the bivariate approach that we took in describing the sample where these factors may not alone impact whether someone identifies as having current, past, or no chronic pain, especially given that when looking within a subgroup reporting chronic pain disparities were found in reports of the experience of pain 15. However, those with current chronic pain did have significantly worse functional outcomes, with medium effect sizes, as measured by the FIM, DRS, and GOS-E. Further research is needed to determine the nature of this relationship between functional outcomes and the experience of chronic pain, as well as exploration of multivariate models where subgroups may be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of a subsample of participants ( n = 621) with chronic pain and TBI from the current study, non-Hispanic Blacks reported greater pain severity and greater pain interference compared with Whites, even after controlling for sociodemographic variables. Older age and less than high school education were also associated with worse pain 15. In the general population, older age, female sex, and lower education have been found to be associated with the experience of both acute pain and chronic pain 16,17…”
mentioning
confidence: 99%
“…For example, several studies revealed racial disparities in TBI care and outcomes. 7,8,10,11 However, race and ethnicity are socially constructed categories that serve as surrogate measures of historical and structural marginalization that may shape TBI care and recovery in myriad, dynamic, and mutually reinforcing ways. 20 As such, including indicators of race and ethnicity alone may be necessary, yet insufficient, for understanding the specific mechanisms underlying disparities in TBI service delivery and recovery.…”
Section: Future Directionsmentioning
confidence: 99%
“…Their data indicated that risk for death by suicide, drug overdose, and opioid overdose was substantially higher among military members who self-identified as “other,” a racial category that may reflect minoritized individuals whose self-conception of racial identity is outside the bounds of standard categories (eg, multiracial). In a study of individuals with moderate-severe TBI and chronic pain, Sander et al8 examined racial disparities in chronic pain-related treatment, pain severity, and pain-related disability. While the authors found no disparities in treatment history, non-Hispanic Black individuals had more severe pain and greater pain-related disability relative to non-Hispanic White individuals.…”
Section: A Summary Of Studies Included In This Topical Issuementioning
confidence: 99%
See 1 more Smart Citation